2003
DOI: 10.1257/089533003772034952
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies: The Law of One Price in Financial Markets

Abstract: The Law of One price states that identical goods (or securities) should sell for identical prices. In financial markets the law of one price is thought to hold almost exactly, and is the basis for much of financial economic theory. We present evidence on several examples of violations of this law, including closed-end country funds, twin shares, dual class shares, and corporate spinoffs. We analyze the causes of these violations, and show they all stem from some limits on the extent to which rational arbitrage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(100 citation statements)
references
References 10 publications
4
93
0
3
Order By: Relevance
“…Shifts in the demand curves indicate shifts in the marginal benefits for investors. Shorting demand may also proxy for informed trading or investor sentiment (Lamont and Thaler 2003). In contrast, shifts in supply are caused by changes in marginal costs.…”
Section: H2mentioning
confidence: 99%
“…Shifts in the demand curves indicate shifts in the marginal benefits for investors. Shorting demand may also proxy for informed trading or investor sentiment (Lamont and Thaler 2003). In contrast, shifts in supply are caused by changes in marginal costs.…”
Section: H2mentioning
confidence: 99%
“…However, the now famous analysis of the price behavior of twin shares of Royal Dutch/Shell and Unilever NV/PLC revealed that even if the true fundamental relative value of two securities is unambiguously known and fixed, the ratio of market prices of such securities may deviate from its fundamental level for a prolonged period. Similarly, researchers discovered that the prices of closed-end funds may substantially deviate from funds' net asset values despite the fact that the two prices should be equal (for review, see Lamont and Thaler, 2003). Since such cases of mispricing received their first major attention in the early 1990s, analogous cases were documented all around the world and asset classes, including the market for derivatives in China (Xiong and Yu, 2011) and the U.S. bond market (Fleckenstein et al, 2014).…”
Section: Price Is Rightmentioning
confidence: 99%
“…Most papers are devoted either to documenting the existence of an anomaly, and trying to fit it into some model, or else to explaining away the observations as outcomes of rational trading. Some references are [3,6,10,13,23,36,37,38,46,48,49]. They provide more references and overviews of the literature in this area.…”
Section: Gilts Mispricings and Other Financial Anomaliesmentioning
confidence: 99%